2016
DOI: 10.1038/nature18634
|View full text |Cite|
|
Sign up to set email alerts
|

Human commensals producing a novel antibiotic impair pathogen colonization

Abstract: The vast majority of systemic bacterial infections are caused by facultative, often antibiotic-resistant, pathogens colonizing human body surfaces. Nasal carriage of Staphylococcus aureus predisposes to invasive infection, but the mechanisms that permit or interfere with pathogen colonization are largely unknown. Whereas soil microbes are known to compete by production of antibiotics, such processes have rarely been reported for human microbiota. We show that nasal Staphylococcus lugdunensis strains produce lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
614
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 718 publications
(684 citation statements)
references
References 58 publications
13
614
0
18
Order By: Relevance
“…As previous studies have illustrated the role of certain Staphylococcus spp. to compete with S. aureus for colonization (27)(28)(29), we proceeded by testing the ability of murine Staphylococcus isolates to compete with S. aureus. Specifically, we chose Staphylococcus residents that were disrupted by antibiotic and antiseptic treatment in our previous experiments for further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies have illustrated the role of certain Staphylococcus spp. to compete with S. aureus for colonization (27)(28)(29), we proceeded by testing the ability of murine Staphylococcus isolates to compete with S. aureus. Specifically, we chose Staphylococcus residents that were disrupted by antibiotic and antiseptic treatment in our previous experiments for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This includes defense against Staphylococcus aureus by unique strains of S. epidermidis (27), S. lugdunensis (28), and most recently, S. hominis (29). Here, it was found that certain individuals are colonized by host-specific Staphylococcus strains with the ability to alter S. aureus colonization patterns.…”
mentioning
confidence: 96%
“…This bacterium that can also be found colonising the nasal snares is said to have the capability to kill S. aureus, as has been reported by various researchers [6] [7] [8]. S. lugdunensis is said to produce lugdunin a novel thiazolidine-containing cycle peptide antibiotic that acts in inhibiting colonisation of S. aureus [6]. These researchers suggested that lugdunin producing S. lugdunensis could be valuable in preventing Staphylococcal infections as well as being effective against strains of MRSA.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, however, attention is drawn to a proposed new antibiotic "Lugdunin" reported to be a product from Staphylococcus lugdunensis. This bacterium that can also be found colonising the nasal snares is said to have the capability to kill S. aureus, as has been reported by various researchers [6] [7] [8]. S. lugdunensis is said to produce lugdunin a novel thiazolidine-containing cycle peptide antibiotic that acts in inhibiting colonisation of S. aureus [6].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation